Numerical analysis of turbulence radiation interaction effect on radiative heat transfer in a swirling oxyfuel furnace. (October 2019) - Yang, Xiao; He, Zhihong; Niu, Qinglin; Dong, Shikui; Tan, Heping
Highlights: TRI is modeled and analyzed in a swirling furnace under oxycombustion conditions. Contribution of radiation to total heat flux on the wall is more than 45%. A local increase of 18% in radiative heat flux is caused by TRI. High O2 concentration highlights the significance of TRI. Increasing swirl number weakens the TRI effect. Abstract: With the application of oxyfuel combustion technology, the status of radiative heat transfer in oxyfuel flames is prominent, and accurate description of it is essential. This study simulates the turbulence radiation interaction (TRI) in a swirling gas-fired furnace to understand the thermal radiation behavior under oxycombustion conditions. Employing the non-gray weighted sum of gray gases model calculates the radiative properties of the participating media and the TRI is modeled. The effects of TRI on the radiative heat transfer in the furnace under different oxycombustion conditions and swirl numbers are analyzed. The results show that the effects of thermal radiation on temperature fields are critical in the gas-fired furnace, especially for oxycombustion condition with high oxygen concentration, and the same is true for TRI effect. With the increase of O2 concentration in O2 /CO2 oxidizer, the radiative heat flux on the chamber wall, the radiative heat flux contribution to total heat flux, and the net radiative heat loss are increased. Increasing swirl number can weaken the TRI effect. It is observed that with 35% O2 in oxidizer, the radiation contribution to heat flux along the entire wall and local increase of radiative heat flux due to TRI effect are almost than 45% and 18%, respectively.